Needs Analysis of Using Tiktok Applications as an Alternative in Music Teaching and Learning - Marlia Munirah Abu Mansor Halimi; Chamil Arkhasa Nikko Mazlan (Program Studi Pendidikan Musik FBS UNP, 2022)
The current direction of education is changing towards digital education, known as information and communication technology (ICT). Educators can choose the right digital platform to use as a teaching aid among media that has a place among Generation Z, one of which is TikTok. Nevertheless, from several selected platforms cannot be separated from the inherent consequences and challenges. This study aims to discuss the use of Tiktok in the music learning process, both as a teacher and a student. The research method used is qualitative analysis to get an in-depth understanding of the use of Tiktok, which focuses on music knowledge. The results of this study show the advantages and disadvantages of using the Tiktok application in Music Education.